Analisis Strategi Pemasaran Produk Deposito Mudharabah Pada PT. BPRS Carana Kiat Andalas KC Padang Panjang - Erizal Candra Efendi; Yuwarman Mansur (IJMA (Indonesian Journal of Management and Accounting), 2022)
Research methodology combines quantitative and descriptive research with the use of the SWOT analysis. That's why the writer has to know the state of the company, including the internal and external factors that affect the marketing approach used. This research's findings suggest that PT. BPRS Carana Kiat Andalas Kantor Cabang Padang Panjang can effectively market its Deposito Mudharabah product by maintaining its strengths and capitalizing on its opportunities, thereby realizing the most effective product-marketing strategy possible through the integration of social media and technological development. Based on the results of a SWOT and combination strategy analysis for marketing Deposito Mudharabah, the following was determined: SO, or enhancing the marketing strategy for Deposito Mudharabah via social media by keeping up with technological developments, engaging in social activism, and increasing public knowledge. products' benefits and outcomes